Gender and education: report of oppression experienced by maroons girls in Paraná - Berg, Juliana; Vestena, Carla Luciane Blum (Revista Hipótese, 2016)
This text brings the perception of researchers about the vulnerability experienced by Maroons girls Wintering Paiol community Tile inside the Paraná about the possible oppression felt in the school environment. A reflection that aimed initially observe the moral judgment of quilombo children and that his journey found reports of lives forgotten by heteronormative and white society. In this perspective, the article presents the results of proposed talks and dilemmas, organized following the clinical method, arguing quilombo identity, gender and ethnicity of girls aged between 10 and 14 years old.